(untitled) (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
This article argues that Fronto’s epistolary pedagogy with Marcus Aurelius exhibits structural affinities with Quintilian’s ideal magister, namely a paternal figure combining authority, affective attachment, individualized guidance, and a graduated programme of exercises. Rather than positing direct influence, the study offers a typological comparison, situating Fronto within imperial educational practices and mapping convergences with the Institutio oratoria (especially Book II). Three results emerge. First, Quintilian’s teacher model hinges on “substituting for the father,” where esteem and affection function as conditions of imitation, character formation, and sustained improvement. Second, the progymnasmata operate as a hinge between technique and ethos: encomia and invectives train style and arrangement while cultivating moral discernment, turning rhetorical practice into a pedagogy of virtue. Third, Fronto’s letters confirm the program in action: vigilant care for the pupil’s well-being, tightly structured assignments, detailed feedback, iterative rewriting (including extended “maxims”), and an intensively affective, yet pedagogically framed, relationship vocabulary. Taken together, Fronto’s correspondence displays a practice that converges typologically with Quintilian’s programme: a paradigmatic model of imperial education in which rhetorical technique and ethical formation are inseparable.